Vivências na pandemia: as reinvenções do trabalho e as interferências no bem-estar docente - Bentancourt, Diego Emanoel Veis (2024)
This research, carried out in the years 2022 and 2023, within the scope of the Postgraduate Program in Public Policies and Organizational Management, at the Federal University of Santa Maria (UFSM), in the research line LP2 - Pedagogical Management and Educational Contexts and linked to the actions of the research group Teaching, School and Teacher Training (DOCEFORM). The aim was to understand how the changes in ways of life caused by experiences during the COVID-19 pandemic impact on teachers' well-being and the organization and development of their work. To this end, our research problem was to answer: How were the changes in ways of life perceived during the COVID-19 pandemic, in particular: how do these changes impact teachers' health, the organization and development of their work in the early years of elementary school in Sant'Ana do Livramento? As a way of organizing the research methodology, we have broken down this problem into three research questions: (1) How were teachers' work organized and developed to meet the demands imposed by the Covid-19 pandemic? (2) What changes did teachers experience during the pandemic in terms of their social and work dynamics? (3) How did teachers perceive the effects of the new ways of organizing their work to meet the demands of the pandemic on their professional well-being? To this end, we adopted a qualitative approach. Our research context was an elementary school located in the city of Sant'Ana do Livramento (RS). As contributions, in addition to expanding the conceptual theoretical field, we also realized, through the narratives and through the analysis of the teachers' work and their forms of organization, development and reconstruction due to the pandemic, to observe and understand the conditioning factors of the wellbeing of these professionals.